Peculiarities of changes in indices of immunological reactivity in experimental allergic alveolitis under adrenalin myocardial injury and their correction with thiotriazoline - Pyndus, Volodymyr (Journal of Education, Health and Sport, 2015)
Pyndus Volodymyr. Peculiarities of changes in indices of immunological reactivity in experimental allergic alveolitis under adrenalin myocardial injury and their correction with thiotriazoline = Особливості змін показників імунологічної реактивності при експериментальному алергічному альвеоліті в умовах адреналінового пошкодження міокарда та їх корекція тіотриазоліном. Journal of Education, Health and Sport. 2015;5(10):185-190. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32603 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A185-190 https://pbn.nauka.gov.pl/works/661368 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. UDK 616.24 – 056.2 – 082.8 Peculiarities of changes in indices of immunological reactivity in experimental allergic alveolitis under adrenalin myocardial injury and their correction with Thiotriazoline Особливості змін показників імунологічної реактивності при експериментальному алергічному альвеоліті в умовах адреналінового пошкодження міокарда та їх корекція тіотриазоліном Volodymyr Pyndus В. Б. Пандус Danylo Halytsky Lviv National Medical University, Lviv, Ukraine Львівський національний медичний університет ім. Данила Галицького, м. Львів, Україна Abstract Allergic diseases cover more than 20% of people living on the earth, among who exogenous allergic alveolitis (AA) occupies a prominent place. However, the frequency of this disease increases and there is a number of complications with not only medical but also socio-economic values. Today the question remains to be not studied that concerns changes of selected indicators of clinical and humoral immunity in the blood for experimental allergic alveoli (EAA) and adrenaline myocardial injury (AMI) and the possibility of their correction with antioxidants. The goal of study was to elucidate peculiarities of changes of immunological reactivity in the EAA in terms of AMI and set the effect of thiotriazoline on them. The study of individual markers of cellular and humoral immunity showed a malfunction of the immune system in the formation of EAA and AMI and set monocristalline the effect of thiotriazolin on the level of T and B-lymphocytes and CIC in blood. Key words: experimental allergic alveolitis, adrenaline myocardial injury, thiotriazolin. Ключові слова: експериментальний алергічний альвеоліт, адреналінове пошкодження міокарда, тіотриазолін.